Studi Pengaruh Rasio Mol Silika terhadap Titania dalam Pembentukan Koordinasi Titanium Tetrahedral dalam Silika-Titania dengan Metoda Solid State - Yuliani, Amelinda; Veronita, Silvi; Pernadi, Niza Lian; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2023)
Titanium tetrahedral coordination shows high activity as a catalyst so that it attracts attention to be researched and developed. In this study, tetrahedral titanium coordination was studied and produced through the Si-O-Ti bond between solid silica precursors and solid titania. Both precursors are mixed in toluene and sonicated for homogeneity. The resulted mixture was calcined at a temperature of 400oC for 8 hours and then characterized with DRS UV-Vis, XRD and FESEM. The results showed that the synthesis sample experienced an increase in tetrahedral titanium fraction from 27% to almost 34%. Characterization with XRD indicates that the diffraction pattern of the resulting sample is very similar to the titania precursor with a crystalline pattern with an anatase and rutile phases. The morphology of the resulting sample showed that silica samples that did not react with titania experienced agglomeration